Effectiveness of intervention programs in reducing plagiarism by university students: a systematic review - Miranda-Rodríguez, Rubén Andrés; Sánchez-Nieto, José Miguel; Ruiz-Rodríguez, Ana Karen (Frontiers in Education, 2024)
Plagiarism in universities is a problem with potential academic, social, ethical, and legal implications. Systematic review research on academic integrity programs, including plagiarism, has been conducted, but few studies have assessed plagiarism. Therefore, this review synthesizes knowledge on the effect of educational interventions designed to prevent or reduce plagiarism by university students. Method: A systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) criteria to analyze experimental or quasiexperimental studies aimed at reducing plagiarism through objective assessments. The search strategy was implemented in Web of Science, PubMed, Scopus, PsycArticles, ProQuest, ERIC, Redalyc, SciELO, and Tesiunam. Results: Six interventions were evaluated, and 1,631 undergraduate students were included pursuing different majors from different universities. The intervention and assessment strategies varied considerably between studies, 5 of which reported a lower plagiarism frequency in the intervention group than in the control group. Conclusions: The results suggest that interventions with practical elements, such as plagiarism detection, paraphrasing, citation skills, in addition to using software to identify similarities, may reduce plagiarism. However, few studies include an objective evaluation, so more research is needed.